Carbon dioxide reforming of methane to syngas: modeling using response surface methodology and artificial neural network - Saidina Amin, Nor Aishah (Penerbit UTM Press, 2005)

(untitled)
1wt% Of Rhodium (Rh) On Magnesium Oxide (Mgo) Catalyst Have Been Investigated For Carbon Dioxide Reforming Of Methane (CORM) With The Effect Of Oxygen. The Effect Of Temperature,O2/CH4 Ratio And Catalyst Weight On The Methane Conversion, Synthesis Gas Selectivity And H2/CO Ratio Were Studied. With The Help Of Experimental Design, Two Mathematical Approaches: Empirical Polynomial And Artificial Neural Network Were Developed. Empirical Polynomial Models Correlation Coefficient, R, Was Above 85%. However, The Feed Forward Neural Network Correlation Coefficient Was More Than 95%. The Feed Forward Neural Network Modeling Approach Was Found To Be More Efficient Than The Empirical Model Approach. The Condition For Maximum Methane Conversion Was Obtained At 850°C With O2/ CH4 Ratio Of 0.14 And 141 Mg Of Catalyst Resulting In 95% Methane Conversion. A Maximum Of 40% Hydrogen Selectivity Was Achieved At 909°C, 0.23 Of O2/CH4 Ratio And 309 Mg Catalyst. The Maximum H2/CO Ratio Of 1.6 Was Attained At 758°C, 0.19 Of O2/CH4 And 360 Mg Catalyst.